Estudo da origem e transferência de metais e metalóides em áreas de manguezal, por meio de análises isotópicas na cadeia trófica e efeitos bioquímicos e morfológicos em Centropomus parallelus Poey, 1860 - Souza, Iara da Costa (2017)
Estuaries and coastal zones are affected by different types of anthropogenic influences derived from harbour activities, industrial and agriculture discharge. Two mangrove areas in two estuarine ecosystems: Bay of Vitória and Santa Cruz in the State of Espírito Santo, Brazil, with different levels of contamination by metals were evaluated to identify the origin and transfer of the metals and metalloids, through the trophic chain to a top-chain organism (the fish, Centropomus parallelus). The concentrations of metals and metalloids were analyzed in the abiotic matrix (sediment, interstitial water, surface water and bottom water) and biotic (samples of plankton and shrimp) to determine the biomagnification of these pollutants along the trophic chain and their origin was determined using isotopic correlations (carbon, nitrogen and lead). At the same time, metal and metalloid concentrations in gills, muscles, liver and kidney of C. parallelus, as well as biochemical biomarkers of exposure and effect in these organs were evaluated. Ultrastructural analyzes were performed on gills, muscles, liver, gonad and kidney of C. parallelus to evaluate metals internalization and subcellular localization. Linear regression was performed for metal accumulated data for all food web to evaluate biomagnification, biodilution or non-interference of the trophic chain in the accumulation of the different metals evaluated. Stable isotope results are interpreted using a new algorithm (K-means; machine learning) to integrate data from the origin and transfer trough the food web; Multivariate statistical analysis were performed to integrate physical, chemical and biological data for C. parallelus tissues. Results of δ13C and δ15N confirmed plankton and trees as the base of the food web; indicated the crab, shrimp and oyster as intermediate levels, and the fish, C. parallelus, was confirmed as the top of the food web. δ15N also indicated different anthropic impacts in the estuaries, with Bay of Victory being impacted by fertilizers. The 87Sr / 86So isotopic ratio showed a highlight influence of marine water on the ecosystems. The lead fingerprint suggests that the atmospheric particulate material is the source of metal contamination in the ecosystems, being strongly influenced by metallurgical activities. The plant-crab-fish trophic chain presented higher biomagnification potential, while biodilution was more observed in the plankton-shrimp-fish and plankton-oyster trophic chains. Ultrastructural analysis of the abiotic and tissues samples of C. parallelus showed the internalization of metallic nanoparticles in cellular structures (vesicles; nucleus) of all organs analyzed. Nanocrystallographic analyzes shown that metallic nanoparticles found were compatible with those found in atmospheric particulate matter. Biomarkers data corroborate as ultrastructural analyzes, suggesting that metal accumulated cannot be all available. Responses and/or absence of them in a given organ show specific sensitivity of organs and tissues to the accumulation of metals. Metal levels in the gills indicate water contamination and decreased organ sensitivity in most metals; muscle was the least reactive tissue. Biochemical responses suggested that the route of metal elimination is through the gills and kidney. Hepatopancreas and kidneys are important organs of detoxification, being C. Parallelus able to support as environmental conditions, however, imposed with energy expenditure that can influence a growth rate and reproduction processes of this species.